Living with Depression: Why Biology and Biography Matter along the Path to Hope and Healing - Serani, Deborah (Rowman & Littlefield Publishers, 2011)
One out of four Americans will experience mental illness in their lifetime; major depressive disorder is the leading cause of disability in the United States for ages 15 through 44. However, only a fraction of those suffering will seek treatment; 25 percent will seek treatment for symptoms. Stigma claims the other 75 percent, wedging depressed individuals into a life of silent suffering. In Living with Depression, Serani outlines the various forms of depression, describes the different treatments, and outlines methods for living with depression and getting the help you or a loved one needs. Tips on how to choose a good therapist, negotiate the labyrinth of healthcare, and minimize stigma are addressed, as is learning how to use biology and biography as tools of empowerment. Listings of national and global resources make this a ready resource for everything you need to know about depression.